2021
DOI: 10.33448/rsd-v10i2.12151
|View full text |Cite
|
Sign up to set email alerts
|

Cuidados voltados aos familiares de pessoas em finitude humana

Abstract: Objetivo: Sumarizar as contribuições da produção científica sobre os cuidados dispensados à familiares de pessoas em finitude humana. Metodologia: Trata-se de uma revisão integrativa da literatura sobre os cuidados voltados para os familiares de pacientes em processo de finitude humana. Resultados: Foram apresentadas duas categorias temáticas: Categoria temática I – Religiosidade e Espiritualidade e Categoria temática II – Redes de apoio formais e informais, que se subdividiu em três subcategorias: Subcategori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Low quality of life was referred by 64.7% of health care professionals and was associated with not having time to talk to patients' relatives. Effective verbal and non-verbal communication are the cornerstones of health care, provide possibilities in decision-making to the patients' relatives, and may reduce stress and disagreements with the health care team and between relatives 19 . In contrast, literature has shown that bereaved relatives who did not receive effective communication during the death and dying process of their relative demonstrate a bad understanding of the clinical aspects of the disease, resulting in wrong decisions, hassles, fear, guilt, and frustration 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Low quality of life was referred by 64.7% of health care professionals and was associated with not having time to talk to patients' relatives. Effective verbal and non-verbal communication are the cornerstones of health care, provide possibilities in decision-making to the patients' relatives, and may reduce stress and disagreements with the health care team and between relatives 19 . In contrast, literature has shown that bereaved relatives who did not receive effective communication during the death and dying process of their relative demonstrate a bad understanding of the clinical aspects of the disease, resulting in wrong decisions, hassles, fear, guilt, and frustration 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Estudos têm investigado os efeitos da religiosidade na promoção do bem-estar mental, incluindo resiliência, coping religioso, sentido de propósito e esperança. Além disso, a religiosidade tem sido identificada como um recurso significativo para lidar com a ansiedade e o medo relacionados à finitude humana (VAIL KE, et al, 2012;DE QUEIROZ AC, et al, 2021).…”
Section: Relação Entre Religiosidade Saúde Mental E Finitude Humanaunclassified